The Role of Lipopolysaccharide on the Electrochemical Behavior of Titanium - Barao, Valentim Adelino Ricardo [UNESP]; Mathew, M. T.; Assunção, Wirley Goncalves [UNESP]; Yuan, J. C.; Wimmer, M. A.; Sukotjo, C. (Sage Publications Inc, 2011)
Lipopolysaccharide (LPS) may induce peri-implantitis and implant failure. However, the role of LPS in titanium (Ti) electrochemical behavior remains unknown. We hypothesized that LPS in saliva with different pHs affects Ti corrosion properties. Thirty-six Ti discs (15 mm x 3 mm) were divided into 12 groups according to saliva pH (3, 6.5, and 9) and Escherichia coli LPS concentration (0, 0.15, 15, and 150 mu g/mL). Electrochemical tests, such as open circuit potential, potentiodynamic, and electrochemical impedance spectroscopy, were conducted in a controlled environment. Data were evaluated by Pearson correlation and regression analysis (alpha = 0.05). LPS and pH affected Ti corrosive behavior. In general, lower pH and higher LPS concentration accelerated Ti corrosion. In the control group, the increase of pH significantly reduced the corrosion rate and increased the capacitance of the double layer. In LPS groups, the decrease of pH significantly increased the corrosion rate of Ti. LPS negatively influenced Ti corrosion behavior. Abbreviations: C(dl), capacitance of double layer; E(corr), corrosion potential; EIS, electrochemical impedance spectroscopy; I(corr), corrosion current density; I(pass), passivation current density; LPS, lipopolysaccharide; OCP, open circuit potential; R(p), polarization resistance; Ti, titanium.
Keywords: titanium; corrosion; Escherichia coli; lipopolysaccharide; electrochemistry